The prohibition of sexual relations in a therapeutic community: as seen by therapists and clients - Prentice, Helena; Konopíková, Michaela; Hricova, Alena (Jihočeská univerzita v Českých Budějovicích, 2023)
This ethnographic study is a critical reflection on what is traditionally one of the cardinal rules within most of the therapeutic communities that are engaged in treating people who are addicted to narcotic drugs. That rule forbids the initiation of sexual relationships and partnership relationships between clients in the community. This study of clients and therapists in one specific community examines how clients perceive the rule that forbids the initiation of intimate relations during treatment, and whether those perceptions change during the course of treatment. It also addresses how therapists view the rule, and the impact it has on their work.The community's clients perceived the prohibition as encompassing more than just physical intimacy and close contact, extending to the formation of profound emotional connections. Each client participating in the study approached the obligation to abide by the restriction on sexual relations in their own unique manner, and devised personal strategies for managing it. The therapists regarded the regulation against sexual involvement as crucial for maintaining the appropriate course of therapy. They emphasized that romantic involvement within the community setting disrupts the group dynamics and has a detrimental effect on the therapeutic process. Similarities and disparities in attitudes toward the rule were identifiable among the clients and therapists. Both groups of respondents were convinced of the rule's significance, as it encourages clients to prioritize themselves and their own treatment.
Zákaz sexuálních vztahů v terapeutické komunitě: jak jej vidí terapeuti a klienti
Keywords: Drug users; Sexual relations; Therapeutic community; Treatment; uživatelé drog; sexuální vztahy; terapeutická komunita; léčba